A comprehensive review on BPA degradation by heterogeneous Fenton-like processes. (19th July 2022) - Nath, Ankurita; Biswas, Subhadeep; Pal, Anjali
Abstract: Synthetic organic pollutants emanating continuously in the ecosystem have become a global concern because of their toxicity and persistent nature. Bisphenol A (BPA) is one such pollutant which threatens public health and safety. It is a monomer used in manufacturing plastics, polycarbonate resins, epoxy resins and is a well-recognised endocrine disruptor mimicking estrogen. BPA leaches into food and beverages stored in containers causing contamination issues. Its widespread exposure and potential toxicity is an environmental health concern. In this review, a systematic investigation has been carried out on the heterogeneous catalysts used for Fenton-like processes for BPA degradation. The Fenton-like reaction is one such reaction that is used for wastewater remediation purposes. The reaction advances through the generation of powerful oxidizing radicals like OH and SO4 – in the presence of a suitable catalyst. The application of various Fenton catalysts, with their distinguished morphological characteristics, oxidizing properties, toxicity analysis, and the present state of the art of BPA degradation by these catalysts, have been documented in the current work. This review also highlights a few challenges and prospects for analysing degradation products of landfill leachate. HIGHLIGHTS: Bisphenol A (BPA) is one of the most common emerging contaminants found often in water bodies. In the present article, Fenton type processes which are known to be a powerful technique for BPA degradation are reviewed. Different types of catalysts based on Fe, Mn, Co, Cu have been covered and the mechanisms are discussed. Graphical Abstract